Answer:
A.
![f(7) = 5(7) + 1\\\\f(7) = 36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1tauste79s9wohey7kiaegz6foauizqou7.png)
B.
![f^(-1)(x) = (x - 1)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xjaf4s48bwgajg5k82nmibxxon4nviy1oo.png)
C.
![f^(-1)(7) =(6)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aw2b7df1tebok0an3fgd7481a9x8wumxcn.png)
D.
![f((6)/(5)) = 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/krn48dv06a76r6amz4br5020ry5o98k975.png)
Explanation:
A. To solve the first part of the problem we must replace
in the function
![f(x) = 5x + 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8k67v9byenlclxtm7sj3sdhqdbdgc0cllt.png)
So:
![f(7) = 5(7) + 1\\\\f(7) = 36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1tauste79s9wohey7kiaegz6foauizqou7.png)
B. In part B we must find the inverse function of
![f(x) = 5x + 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8k67v9byenlclxtm7sj3sdhqdbdgc0cllt.png)
To find the inverse function do
![y = f(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4hz2zfxlqmcq6pfatrbeu6f5p0zwvmwuzs.png)
![y = 5x +1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hk2ncb8mtxbujeyq9frs8cvf6xp6465132.png)
Now clear the variable x.
![(y - 1)/(5) = x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o39af3zkkve2rzb09mn2jyqvvdxef3ujsa.png)
Replace x with y.
![y = (x - 1)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nsqzddsmi9anyl4j7uxobnzi93kib3pwy0.png)
Finally
![f^(-1)(x) = (x - 1)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xjaf4s48bwgajg5k82nmibxxon4nviy1oo.png)
C. Now we take the inverse function found above and replace
![x = 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/583yuwvjl9ywi8bbwfijewrjw16sriakkg.png)
![f^(-1)(7) = (7 - 1)/(5)\\\\f(7) = (6)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/227976h7m45nmh2cuco7x1un0zi3wpq1l1.png)
D. Now we substitute
in the original function.
![x = f( f^(-1)(7))\\\\f^(-1)(7) = (6)/(5)\\\\ x= f((6)/(5) )\\\\f((6)/(5)) = 5((6)/(5)) + 1\\\\f((6)/(5)) = 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nsqq9nt3fp2tnst8iiws4mq0or1jmxiu3h.png)